Optical and photovoltaic properties of thieno[3,2-b]thiophene-based push–pull organic dyes with different anchoring groups for dye-sensitized solar cells - Fernandes, Sara Sofia Marques (2017)
The effect of anchoring groups on the optical and electrochemical properties of triphenylamine-thienothiophenes, and on the photovoltaic performance of DSSCs photosensitized with the prepared dyes, was studied using newly synthesized compounds with cyanoacetic acid or rhodanine-3-acetic acid groups. Precursor aldehydes were synthesized through Suzuki cross-coupling, whereas Knoevenagel condensation of these with 2-cyanoacetic acid or rhodanine-3-acetic acid afforded the final push–pull dyes. A comprehensive photophysical study was performed in solution and in the solid state. The femtosecond time-resolved transient absorption spectra for the synthesized dyes were obtained following photoexcitation in solution and for the dyes adsorbed to TiO2 mesoporous films. Information on conformation, electronic structure, and electron distribution was obtained by density functional theory (DFT) and time-dependent DFT calculations. Triphenylamine–thienothiophene functionalized with a cyanoacetic acid anchoring group displayed the highest conversion efficiency (3.68%) as the dye sensitizer in nanocrystalline TiO2 solar cells. Coadsorption studies were performed for this dye with the ruthenium-based N719 dye, and they showed dye power conversion efficiencies enhanced by 20–64%. The best cell performance obtained with the coadsorbed N719 and cyanoacetic dye showed an efficiency of 6.05%.